Application Prospect Analysis of 3D Printing Technology in Industrial Manufacturing - Zhang, Qiang; Li, Wenjie; Yang, Jifeng (International Journal of Computer Science and Information Technology, 2024)
This paper deeply and comprehensively discusses the application status of 3D printing technology in the field of industrial manufacturing and the broad development prospects in the future. Through the in-depth analysis of the principle and characteristics of 3D printing technology, the significant advantages of 3D printing in industrial manufacturing are clearly expounded. At the same time, the specific application examples of the technology in aerospace, automotive, medical and other key and important industrial fields are studied in detail and systematically, and the possible expansion direction of the future is scientifically and reasonably predicted. The purpose is to provide valuable and instructive reference for the related research and practice in the field of industrial manufacturing.